2018
DOI: 10.21163/gt_2018.131.05
|View full text |Cite
|
Sign up to set email alerts
|

Geomedia Role for Mountain Routes Development. Mesehe and Pisoiu Waterfall Comparative Study

Abstract: ABSTRACT:This study discusses a tropical and a temperate forest route development to Mesehe and Pisoiu Waterfall supporting sustainable tourism development in Pohsanten Community, Bali, Indonesia and Bistra, Romania. It is a qualitative study using a combination of observation, direct participation and non-structured interviews as data collecting methods. Geo-data was collected during forest expeditions, interactions and interviews with local community members who participate in tourism. Re-establishing the ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 12 publications
(31 citation statements)
references
References 15 publications
1
30
0
Order By: Relevance
“…The effectiveness of Geomedia techniques is also reflected in the evolution of peer to peer property rental industry in Bran (0.196/9-AG, 0.174/8-GC) and Sighișoara (0.195/8-AG, 0.171/7-GC), in accordance to Ernawati et al, (2018) who showed the importance of the geo-referenced media for the local community-based tourism development which can use the Airbnb website platform, Facebook geo-tagged posts or Google Earth pinned locations to better valorize their resources. Many inhabitants rent their homes in Airbnb online accommodation system.…”
Section: Sighișoara and Bran Geosystems` Effectivenessmentioning
confidence: 90%
See 4 more Smart Citations
“…The effectiveness of Geomedia techniques is also reflected in the evolution of peer to peer property rental industry in Bran (0.196/9-AG, 0.174/8-GC) and Sighișoara (0.195/8-AG, 0.171/7-GC), in accordance to Ernawati et al, (2018) who showed the importance of the geo-referenced media for the local community-based tourism development which can use the Airbnb website platform, Facebook geo-tagged posts or Google Earth pinned locations to better valorize their resources. Many inhabitants rent their homes in Airbnb online accommodation system.…”
Section: Sighișoara and Bran Geosystems` Effectivenessmentioning
confidence: 90%
“…The datasets analysis and attributes particular assessment was done using INIS Viewer, Google Maps and Google Earth internet platforms. Comparative analysis revealed Geosystem`s components properties, significantly contributing to the unique attributes identification (Croitoru et al, 2013;Lapenta, 2011;Ernawati et al, 2018;Zheng et al, 2010). Based on the Romanian Dracula phenomena, this research attempts to emphasize the importance of the local Geosystems` unique attributes and predict future wider applicability of the Geomedia techniques.…”
Section: Methodsmentioning
confidence: 98%
See 3 more Smart Citations